MEMULIAKAN PELAYANAN DAN MEMBUMIKAN PERLINDUNGAN HUKUM BAGI KONSUMEN - Tri Wahyuni (Pusjar SKPP Lembaga Administrasi Negara, 2010)
Service is the most important thing in organization which is run in either private service or government service. Many ways have been done by organization to give the best service for consumer satisfaction. One indicators of service successfulness is there is not any complaint from customer for the service which they got. Even thought if there is complaint, as a good organization, it has to be accepted and it is able to be solved well. Service is as a part from the servive itself. In other word, it is not separated from service that was given before. In many service cases usually consumers are in weak position as an effect from service that was given precisely caused consumer lost their right. For example in Prita Mulyasari’s case, she had to be willing lost her freedom for couple days because she was arrested in jail for her complaint by an email. She was not satisfaied because of the service dissartisfaction. Learning from Prita’s case, we as Indonesian consumer, it is the right time to recognice our right in order to get and to demand the best service without frightened. Keyword: Service, Protection, and consumer